Computational fluid dynamics to reach a high-fidelity simulator of performance in rowing - Leroyer, A.; Barré, S. (Proceedings of the 10th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2022)
The massive growth of computational power and the advances of the numerical models make the use of numerical simulations to help analysing and improving sport performance achievable. However, it is still challenging because the physical configurations generally involved complex coupled problems and because human is part of the system. Furthermore, elite athletes already operate near an optimal point. As a consequence, the modelization of all the phenomena that come into play has to be accurate enough to be useful and relevant when the objective is to analyse interactions and to give reliable trends while varying some parameters. The case of rowing is presented here, through the development of SPRing (Simulator of Performance in Rowing), a high-fidelity simulator of the global system "boat-oars-rower(s)" coupled with the resolution of the Reynolds-Averaged Navier-Stokes equations to provide fluid forces acting on it.